2004
DOI: 10.1369/jhc.4a6260.2004
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Neointimal Vascular Smooth Muscle Cellularity in Atheroma by Plasminogen Activator Inhibitor Type 1 (PAI-1)

Abstract: S U M M A R YRupture of vulnerable atheroma often underlies acute coronary syndromes. Vulnerable plaques exhibit a paucity of vascular smooth muscle cells (VSMCs) in the cap. Therefore, decreased VSMC migration into the neointima may predispose to vulnerability. The balance between cell surface plasminogen activator activity and its inhibition [mediated primarily by plasminogen activator inhibitor type 1 (PAI-1)] modulates migration of diverse types of cells. We sought to determine whether increased expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 36 publications
3
35
0
2
Order By: Relevance
“…8,20 In the present studies, greater proliferation was demonstrated in VSMCs from PAI-1 transgenic mice (SM22-PAI ϩ ). After 6 days in culture, the average number of SM22-PAI ϩ VSMCs was 2.3Ϯ0.4-fold greater than control VSMCs ( Figure 1A …”
Section: Growth and Proliferation Of Vsmcs From Sm22-pai ؉ Micesupporting
confidence: 54%
See 3 more Smart Citations
“…8,20 In the present studies, greater proliferation was demonstrated in VSMCs from PAI-1 transgenic mice (SM22-PAI ϩ ). After 6 days in culture, the average number of SM22-PAI ϩ VSMCs was 2.3Ϯ0.4-fold greater than control VSMCs ( Figure 1A …”
Section: Growth and Proliferation Of Vsmcs From Sm22-pai ؉ Micesupporting
confidence: 54%
“…Their observation of decreased neointimal formation after injury when PAI-1 expression was restored with adenoviral gene transfer 29 is consistent with our previous observation that increased expression of PAI-1 inhibits VSMC contribution to neointimal formation presumably by inhibiting migration. 8 Differing effects of PAI-1 on the in vitro proliferation of aortic endothelial cells 33 and VSMCs 34 are likely to be a reflection of differences in cell type, culture conditions, genotypes, and experimental design. Nevertheless, these results are consistent with the observation that increased intracellular expression PAI-1 promotes proliferation of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides modulating thrombolysis, fibrinolytic activity likely influences the progression of atherosclerotic lesions [3]. Overexpression of PAI-1 may also promote the development of weak plaques with thin fibrous caps by inhibiting both u-PA receptor-and integrin-mediated cell adhesion and migration [4,5]. Therefore, increased PAI-1 levels may play a crucial role in the occurrence of MI by affecting both atheroma and thrombosis.…”
Section: Introductionmentioning
confidence: 99%